Potential inhibitory activities of phytoconstituents in Salvia miltiorrhiza against coronary heart disease drug targets using docking and ADMET studies - Thi Thuy Duong, Man; Ngoc Long, Nguyen; Hai Son, Pham; Thi Hoai Van, Tran; Bach, Long Giang; Long, Pham Quoc; Viet Hai, Ha; Tien Lam, Do; Thi Hong Minh, Pham; Thi Thuy Huong, Le (Vietnam Journal of Science and Technology, 2024)
Coronary heart disease (CHD) is one of the leading causes of death worldwide. The effectiveness of the current drugs is still restricted due to high side effects; thus, it is urgently needed to discover novel compounds for drug development. In the field of drug discovery research, the main target receptors for chemotherapy are identified as ACE, PPAR-γ, HMGR, COX-2, and thrombin. In this study, docking simulations were performed for phytoconstituents of Salvia miltiorrhiza Bunge in searching for compounds with potential inhibitory activities against these proteins. As a result, six compounds were suggested as potential multitarget inhibitors and could be considered for further drug development studies based on docking conformation and ADMET property analysis.